2021
DOI: 10.3390/s21134259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patellar Tendinopathy on Isokinetic Knee Strength and Jumps in Professional Basketball Players

Abstract: Patellar tendinopathy is characterized by tendon pain which may reduce the level of performance. This study’s main aim was to compare isokinetic knee strength and jump performances at the start of the sport season between players with patellar tendinopathy and those without. Secondary aims were to assess the relationship between knee strength and jump function. Sixty-two professional basketball players were enrolled (mean age: 25.0 ± 4.0). All players performed knee isokinetic measurements, single leg counterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 54 publications
2
11
0
1
Order By: Relevance
“…However, as previously published by Dauty et al [26] in professional basketball players, our results support a significant decrease in the quadriceps strength in the case of PT. Concerning the hamstrings, we found a significant decrease in the strength at 60 • /s and only a trend toward a difference at 180 • /s, whereas other studies in basketball players and in runners showed no significant difference for this group of muscles [13,26]. This finding seems of great interest because it means that rehabilitation should also focus on hamstrings and not only on quadriceps in the case of PT.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, as previously published by Dauty et al [26] in professional basketball players, our results support a significant decrease in the quadriceps strength in the case of PT. Concerning the hamstrings, we found a significant decrease in the strength at 60 • /s and only a trend toward a difference at 180 • /s, whereas other studies in basketball players and in runners showed no significant difference for this group of muscles [13,26]. This finding seems of great interest because it means that rehabilitation should also focus on hamstrings and not only on quadriceps in the case of PT.…”
Section: Discussionsupporting
confidence: 92%
“…The impairment of isokinetic muscle strength remains unclear as only a few studies reported no significant difference in isokinetic quadriceps muscle strength when comparing a group with PT and a control group of runners or a mix of volleyball, basketball and handball players [13,32]. However, as previously published by Dauty et al [26] in professional basketball players, our results support a significant decrease in the quadriceps strength in the case of PT. Concerning the hamstrings, we found a significant decrease in the strength at 60 • /s and only a trend toward a difference at 180 • /s, whereas other studies in basketball players and in runners showed no significant difference for this group of muscles [13,26].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations